Meningkatkan Kepercayaan Diri Dalam Maharatul Kalam Melalui Debat Bahasa Arab - Aliyah, Siti Alfi; Hidayanti, Primasti Nur Yusrin (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2024)
Speaking skills (Maharah Kalam) in Arabic are indeed very important in language proficiency, especially for Arabic learners. Proficiency in speaking is the goal of learning Arabic. Learning Arabic with the debate method, in addition to increasing knowledge about Arabic, can also increase confidence in speaking skills. This study aims to determine the level of confidence in Maharah Kalam and the strategies used to improve Maharah Kalam in the Arabic debate. The focus of this research is on members of al-Motayat who is an Arabic debate forum in the Arabic Language and Literature department of UIN Sunan Kalijaga Yogyakarta. While this type of research is quantitative descriptive with data collection techniques through interviews, observation, and taking notes. The results of this study indicate that Arabic debate can improve proficiency in speaking Arabic, which is evidenced by the results of interviews that confidence in Maharah Kalam with debate increases from 30% to 70%.